Benefits of creatine as a nutritional supplement - Aragão, Graziela de Carvalho (2022)
Introduction: Creatine has been increasingly used to optimize the physical condition in strength training, increase muscle mass and association of its supplementation as a dietary supplement and for aesthetic purposes. This study will contain data based on a literature search in order to analyze the available information on the subject. This is a review that will include data from the analysis of information from academic sites such as Scielo and Pubmed, and to integrate ro content, books and articles from the area of sports nutrition will be used as inclusion criteria. All will guide the theoretical development of the research presented in order to cover the topics addressed in a descriptive way. Specific Objective: To analyze the chemical characteristics present in creatine, investigate the effects of creatine supplementation on body composition of bodybuilding practitioners, and verify a diet and supplementation strategy allied to bodybuilding practice. General Objective: To present the action of creatine and its benefits as a supplement during physical activity allied to a balanced diet and the action in the body and its benefits as a supplement during physical activity, highlighting the most frequently obtained results. Conclusion: Through the development of this research, it is possible to identify the positive effects of creatine supplementation through literature, respecting the individuality of each person and making conscious use of this ergogenic resource.